Relationships between the Occlusal Force and Physical/Cognitive Functions of Elderly Females Living in the Community - Hirao, Aya (The Society of Physical Therapy Science, 2014)
[Purpose] The present study, was conducted to examine the occlusal force and physical, cognitive, and attentional functions of elderly females living in the community to evaluate the significance of measuring the occlusal force. [Subjects and Methods] The number of subjects was 104. The Occlusal Force Meter GM10 was used to measure their occlusal force. Their physical functions were assessed using eight examinations, including the 30-second Chair Stand Test, and the cognitive functions of the Mini-Mental State Examination and attention functions of the Trail Making Test. [Results] Significant correlations were noted between the occlusal force and all measurements, except for the results of forward bending in a sitting position. Multiple regression analysis was conducted with the occlusal force as an objective variable, and significant partial correlations were noted with the 30-second Chair Stand Test. [Conclusion] These results suggest that it is necessary to provide the elderly with comprehensive support focusing on maintaining their occlusal force, as a nursing care-prevention measure, to help them continue to live a healthy, independent life.